Efektivitas Psikoedukasi untuk Peningkatan Literasi Depresi - Omar Syarief Natasubagyo; Sri Kusrohmaniah (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to see the effectivity of psychoeducation to increase depression literacy. It was hypothesized that psychoeducation might increase depression literacy in treatment group higher than the control group. Using randomized pretest and posttest control group experimental design and multiple-choice depression literacy test to obtain data, 35 participants consisted of non-psychology/medicine student with age ranging from 18 – 24 years old were randomly placed at treatment and control group. Using Mixed ANOVA to analyze the data, the results showed a non-significant effect of group (F = 1.965; p = 0.171). However, there was significant interaction effect (F = 8.665; p = 0.006). Mean differences were higher in the treatment group at 4.688 compared to control group at 1.684. This showed that psychoeducation increase depression literacy, with higher enhancement at treatment group. Thus, the hypothesis of the study was accepted